Temporalities for, of, and in Planning: Exploring Post-Growth, Participation, and Devolution Across European Planning Reforms - Lucía Cerrada Morato; Agnieszka Zimnicka; Judi Wilson (Urban Planning)
In the wake of the Covid-19 pandemic and the acceleration of climate change, many governments are turning to their planning systems to explore how national planning reform can help them address their current crisis. Time across planning reforms appears as a central dimension, building on governments’ long-term ambitions to speed planning. While academic normative debates argue in favour of faster and/or slower changes to planning as inherently good or bad, this article draws on a comparative analysis of national planning reforms across three European countries to critically examine how time is being mobilised and with what objective. Through an analytical framework that seeks a more holistic understanding of the planning process, we argue that temporalities in planning are relational. Across the three cases, we can see how the generation of consensus depoliticises the use of time, and it is generally used to advance regressive agendas. We argue that despite ambitions to make planning more responsive and participatory at the local level, planning reforms (a) reduce the influence of public participation while strengthening private property rights; (b) are used to territorialise sectoral, top–down, and long-term agendas with no consideration of the timely and situated concerns and visions of residents and communities; and (c) are underpinned by a pro-growth and rapid urbanisation agenda that ignores sustainability debates.